The Deposition - Duval, Pete (University of Massachusetts Press, 2021)
An insurance lawyer driving across Iowa engages a wounded, hitchhiking priest in a metaphysical debate. A vacationing air traffic controller with a penchant for Saint Francis of Assisi is bitten by an ancient parrot. The Marxist owner of a Florida curiosity shop confronts a local church community's rising anger over a jarred fetus, while a fasting husband of an evangelical minister holds bloody communion with the leader of a suburban coyote pack and a Catholic cable news cameraman tracks a missing stigmatist through a Caribbean port city. As cosmic struggles play out against the backdrop of forgotten strip malls, suburban cul-de-sacs, and grimy cities, guidance comes from the unlikeliest of sources. In prose both dreamlike and vivid, the characters in Pete Duval's second collection navigate paths through a landscape of vestigial faith and nagging doubt.